MARKETING STRATEGY USING SWOT ANALYSIS (CASE STUDY: STIMA IMMI) - Aglom Mel Yoksam Neolaka; Mega Faulina; Pepih Akromah; Tri Astuti Novilasari; Reimond Hasangapan Mikkael Napitupulu (SEAN Institute, 2023)
This study analyzes the marketing strategy at STIMA IMMI. This type of research is descriptive research. Data was collected through documentation techniques and in-depth interview techniques sourced from informants. The data were analyzed using quantitative analysis and qualitative analysis. The results of the study show that the corporate level strategy implemented by STIMA IMMI is based on the analysis that has been carried out is a diversification strategy, by increasing the number of educational service products that are no different from the main product. Functional level strategies to support diversification, namely: product positioning strategy, product diversification, penetration pricing strategy, promotions that can shape the image of potential consumers and are periodic, educational service products as close as possible to consumers,in the Civil Service Police Unit of Solok City but it has not been optimal.